Outdoor dissolution of detonation residues of three insensitive munitions (IM) formulations. (September 2015) - Taylor, Susan; Dontsova, Katerina; Walsh, Marianne E.; Walsh, Michael R.
Graphical abstract: (a) Image of a low order detonation, (b) size distributions of particles scattered by IM rounds compared with those for TNT and Comp B rounds and (c) quasi-linear dissolution of DNAN as a function of water volume used to estimate particle life spans. Highlights: Detonation residues of IMX 101, IMX 104, and PAX 21 differ in size. Size distributions are likely controlled by the initial explosive mass in the rounds. These formulations break more easily than do conventional explosives. Centimeter-sized DNAN pieces have quasi-linear dissolution rates. Abstract: We seek to understand the environmental fate of three new insensitive munitions, explosive formulations developed to reduce the incidence of unintended detonations. To this end, we measured the size distribution of residues from low order detonations of IMX 101, IMX 104, and PAX 21-filled munitions and are studying how these three formulations weather and dissolve outdoors. The largest pieces collected from the detonations were centimeter-sized and we studied 12 of these in the outdoors test. We found that the particles break easily and that the dissolution of 2, 4-dinitroanisole (DNAN) is quasi-linear as a function of water volume. DNAN is the matrix and the least soluble major constituent of the three formulations. We used DNAN's linear dissolution rate to estimate the life span of the pieces. Particles ranging in mass from 0.3 to 3.5 g will completely dissolve in 3–21 years given 100 cm y −1 precipitation rates.